An Exploratory Study of the Determinants of the Quality of Strategic Decision Implementation in Turkish Industrial Firms. (December 2014) - Elbanna, Saïd; Thanos, Ioannis C.; Colak, Mustafa
This paper investigates the determinants of quality of decision implementation. By drawing on a sample of 116 firms located in Turkey, the authors test whether the features of important team processes (i.e. trust and participation), of the organisation (i.e. past performance) and of implementation (i.e. its speed and uncertainty) exert an influence on the quality with which decisions are implemented. Exploratory and confirmatory factor analyses were used to test the validity of the measures, while path analysis was used in hypotheses testing. The results suggest that quality of decision implementation is positively related to trust, participation and past performance, and negatively to implementation speed and uncertainty. The implications of these findings for theory, practice and general management are discussed.